(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
In recent million years, the scale of the negative impact on the environment of economic activity had a feature which was long limited. The development of agriculture in some parts of the world has been accompanied by salinization of soils, shallowing of rivers, deforestation and drying of seas. In the nineteenth century, the state of the environment and natural resources began to pose a threat to human life, as a society based on agricultural production shifted to an industry that began to dominate industrial production. The development of modern communication and information technologies in the last decades of the twentieth century has led to the globalization of the world economy